Application of Problem Solving in Indonesian Language Subjects at Muhammadiyah 2 Middle School in Taman - Sulikah Tri Handayani; Yayuk Fauziah; Eni Fariyatul Fahyuni (International Consortium of Education and Culture Research Studies, 2020)
Methods of problem solving is problem-based learning. Can be referred to a learning approach that uses problem as context for the student to learn how to think critically to solve problems, and to acquire the knowledge and the concept of the material being taught.This study aims to apply learning with problem solving method on subjects Indonesian and enhance students' skills in understanding and mastering the material being taught. This study used a qualitative approach that is both a description of the meaning of the subject of a study involving 34 students in one class. Data were collected by observation, interview, and documentation. The results showed that an increase in students in solving problems until the appropriate retrieval solutions.